(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
This research examines the notion of equivalence in translation by observing Muluki Ain, 1963 of Nepal. It explores different types of equivalences used in the English translation of the Ain. Maintaining equivalence semantically and pragmatically with equivalent effects between the source language (SL) law and the target language (TL) law is challenging to the legal translator. This study searches how the SL (Nepali) law is translated equivalently into the TL (English) to communicate with the target readers. The language and legal system between Nepali and English are different and face cultural interference in conveying the SL messages equally in TL for the TL readers. This research uses Nida’s formal and dynamic equivalence, and Becker’s different types of equivalences at word level, above word level, grammatical equivalence, textual equivalence, and pragmatic equivalence for the theoretical framework. The primary data are collected from Muluki Ain, 2020 (1963), and its authorized English translation version. The secondary data are taken from the critical and theoretical view of translation equivalence. It uses the corpus-assisted method as the research methodology to find the textual and contextual equivalence between SL and TL. The major finding of the research is that institutional translators have applied different types of equivalences to convey SL legal messages into the TL. It concludes that a translation needs to be equivalent in every aspect of the language pair.